2020
DOI: 10.3390/biomedicines8100382
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Anticancer Uses of the Active Principles of “Rhopalurus junceus” Venom

Abstract: The Rhopalurus junceus is a scorpion belonging to the Buthidae family that finds its habitat in Cuba. This scorpion is known by the common name of “Blue Scorpion”. The venom is used on the island of Cuba as an alternative cure for cancer and, more recently, in the research of active components for biomedicine. Recently, the venom has been tested in several studies to investigate its effects on cancer cell lines, and the initial results of in vitro studies demonstrated how this poison can be effective on certai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
(46 reference statements)
1
3
0
Order By: Relevance
“…However, this study also demonstrated the differential expression of specific microRNAs among DPSC isolates, revealing an association with miR-21 expression and more rapid growth and proliferation. This may support other observations of miR-21 and the role this microRNA plays in the development and progression of rapidly dividing cancers, however, most other previous studies in DPSC have only demonstrated correlations between miR-21 expression and anti-inflammatory pathways (Dioguardi et al, 2022;Singh et al, 2021;Nara et al, 2019;Ayadilord et al, 2021). Other researchers have recently reported that miR-21 may potentially function in DPSC via interactions with STAT3 to facilitate odontoblast differentiation (Xu et al, 2018).…”
Section: Discussionsupporting
confidence: 86%
“…However, this study also demonstrated the differential expression of specific microRNAs among DPSC isolates, revealing an association with miR-21 expression and more rapid growth and proliferation. This may support other observations of miR-21 and the role this microRNA plays in the development and progression of rapidly dividing cancers, however, most other previous studies in DPSC have only demonstrated correlations between miR-21 expression and anti-inflammatory pathways (Dioguardi et al, 2022;Singh et al, 2021;Nara et al, 2019;Ayadilord et al, 2021). Other researchers have recently reported that miR-21 may potentially function in DPSC via interactions with STAT3 to facilitate odontoblast differentiation (Xu et al, 2018).…”
Section: Discussionsupporting
confidence: 86%
“…Research on Rhopalurus junceus venom demonstrated the cytotoxic effect of this venom against cancer cell lines of epithelial origin (Dioguardi et al, 2020). Scorpion venom Androctonus Australis has shown that has anti-tumor activity on HCT116, HepG2, MCF-7, and PC-3 as cancer cell lines (Nafie et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The Rhopalurus juncues (also known as blue scorpion) is a type of scorpion inhabiting in Cuban island and is a member of the Buthidae family [10]. The SV has been researched for its pharmaceutical potential in clinical cancer treatments as a branch of biomedicine.…”
Section: Scorpion Venommentioning
confidence: 99%